Enhancing Safety of PCG Personnel Working on Vessel’s Enclosed Spaces through Capacity Building Program - Denis R. Rapal (International Journal of Multidisciplinary: Applied Business and Education Research, 2026)
The rising cases of shipboard enclosed space accidents and deaths has increased the significance of providing the safety of maritime personnel. This paper evaluates awareness and knowledge levels of Philippine Coast Guard (PCG) staff on enclosed space entry, in three key areas, namely, regulations, equipment, and competence. It seeks to suggest an organized capacity-building initiative to improve safety measures and operational readiness on PCG ships. The paper is designed as a mixed research with a concurrent triangulation design. It gathers both quantitative data by surveying 312 PCG personnel on board ships with the help of a structured examination tool and qualitative information by conducting in-depth interviews with five veteran seafarers of the commercial ships. The researcher analyzed the results of the examination with the help of descriptive statistics and frequency distribution and conducted thematic content analysis of the transcript of the interviews. The results indicate that despite the majority of PCG respondents expressing overall knowledge of the dangers of enclosed spaces, there are still considerable knowledge gaps. Regarding regulations, most respondents demonstrate a minimum level of knowledge and are not familiar with the applicable international regulations. The level of knowledge of equipment is generally satisfactory, but the respondents lack the skills of using and preparing special tools needed in rescue and emergency cases. Competence is considered the weakest area, and the percentage of the personnel that exhibits poor knowledge of hazard identification, electrical safety, and emergency responses is significant.